Chosen aspects of defining technical wear of buildings - Konarzewska, Malgorzata; Konarzewski, Artur (Technological and Economic Development of Economy, 2006)
The article discusses the problem of defining borderline values of technical wear of a building and/or its components. Formulas and methods of defining wear have been highlighted, and an example has been presented, where the calculations were made according to proportionality formulas: Ross and Unger, Romstorfen and Eytelwein. While analysing results, some differences have been pointed out in the assessment of the degree of wear, depending on the time lapse and selection of a calculation formula. Selecting an inappropriate calculation procedure (depending on the focus on an element), and incorrect manner of defining technical life span of an element or a whole building leads to serious errors. The justifiability of the above statement has been proved in the summary, where a comparison of element use, according to different calculation formulas, has been presented in a graphic form.Techninio pastatų nusidėvėjimo įvertinimo aspektaiSantrauka. Straipsnyje diskutuojamos pastatų ar jų komponentų techninio nusidėvėjimo tikslumo įvertinimo problemos. Aprašyti nusidėvėjimo įvertinimo metodai ir formulės, pateikti pavyzdžiai, kuriuose skaičiuota pagal proporcingumo, Rosso ir Ungurio, Romstorfeno ir Eytelweino formules. Tyrimai atskleidė, jog atsižvelgiant į pasirinktą laikotarpį ir skaičiavimo formules, gautos nusidėvėjimo reikšmės skiriasi. Pasirinkus netinkamą elemento eksploatacijos trukmės skaičiavimo metodą, gaunamos nemažos paklaidos. Tai rodo įvairių skaičiavimų metodų lyginamoji grafinė išraiška.Reikšminiai žodžiai: techninis nusidėvėjimas, techninės pastatų būklės nustatymas, techninės būklės nustatymo metodai, techninė elementų būklė, elemento amžius, proporcingumo formulė, Ungerio ir Rosso formulė, Ramstorfeno formulė, Eytelweino formulė, senėjimą įvertinantis metodas.First Published Online: 21 Oct 2010